2015
DOI: 10.1161/circresaha.116.303613
|View full text |Cite
|
Sign up to set email alerts
|

The GSK-3 Family as Therapeutic Target for Myocardial Diseases

Abstract: GSK-3 is one of the very few signaling molecules that regulate a truly astonishing number of critical intracellular signaling pathways. It has been implicated in a number of diseases including heart failure, bipolar disorder, diabetes, Alzheimer’s disease, aging, inflammation and cancer. Furthermore, a recent clinical trial has validated the feasibility of targeting GSK-3 with small molecule inhibitors for human diseases. In the current review we will focus on its expanding role in the heart, concentrating pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 84 publications
1
159
0
1
Order By: Relevance
“…Indeed, optimism for developing GSK-3 inhibitors for clinical use remains high for treatment of a variety of severe pathological conditions including progressive central nervous system disorders, cancer, metabolic disorders and even ischemic cardiac injury. 5,1921 Current clinical trials are testing GSK-3 inhibitors for chronic treatment of patients with Alzheimer’s disease and supranuclear palsy. 19,20 Although safety was achieved in two Phase-1 clinical trials, our current data provides a cautionary note for the potential consequences of chronic pharmacological GSK-3 inhibition in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, optimism for developing GSK-3 inhibitors for clinical use remains high for treatment of a variety of severe pathological conditions including progressive central nervous system disorders, cancer, metabolic disorders and even ischemic cardiac injury. 5,1921 Current clinical trials are testing GSK-3 inhibitors for chronic treatment of patients with Alzheimer’s disease and supranuclear palsy. 19,20 Although safety was achieved in two Phase-1 clinical trials, our current data provides a cautionary note for the potential consequences of chronic pharmacological GSK-3 inhibition in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Although the name is derived from its role in glycogen metabolism, recent studies have revealed that GSK-3 is a multifunctional enzyme regulating many biological processes in the heart, including gene expression, hypertrophy, development, proliferation, fibrosis, and apoptosis, being a therapeutic target for myocardial diseases (4,17). Knockout (KO) of GSK-3␤ in the mouse whole body is embryonic lethal due to severe liver degeneration and obliteration of the ventricular cavity via cardiomyocyte hyperproliferation (14).…”
Section: New and Noteworthymentioning
confidence: 99%
“…Apoptosis of cardiomyocytes is known to be an important mechanism of I/R injury [3,4,5]. Accumulating evidence has shown that apoptosis of cardiomyocytes is suppressed by glycogen synthase kinase-3β (GSK-3β) [6,7,8]. Therefore manipulation of GSK-3β is a promising strategy for myocardial protection in I/R injury.…”
Section: Introductionmentioning
confidence: 99%